Krystian Lupa and the Pop Culture Icons, i.e. "Persona. Marilyn" and the Mythical Body in Flames - Gołos-Dąbrowska, Katarzyna (Załącznik Kulturoznawczy, 2024)
The article presents an analysis of Krystian Lupa's performance “Persona. Marilyn” in terms of the symbolism of fire that appears in the play. The play itself is a fantasy about the last days of Marilyn Monroe's life, who, through her work on the planned role of Grushenka in The Brothers Karamazov, intends to find her identity and rediscover herself as an actress. The key to interpreting the play lies in the final scene of the performance, in which Marilyn Monroe burns laid on a catafalque. The text constitutes an attempt to flesh out possible interpretations of this scene, using references to the broad symbolism of fire in culture, particularly based on the thought of Gaston Bachelard (fire as a transfer to the sacred zone, sacrifice, purification, destruction, desire).